The Dynamics of Plasma Membrane, Metabolism and Respiration (PM-M-R) in Penicillium ochrochloron CBS 123824 in Response to Different Nutrient Limitations—A Multi-level Approach to Study Organic Acid Excretion in Filamentous Fungi - Vrabl, Pamela; Schinagl, Christoph W.; Artmann, Desirée J.; Krüger, Anja; Ganzera, Markus; Pötsch, Ansgar; Burgstaller, Wolfgang (Frontiers in Microbiology, 2017)
Filamentous fungi are important cell factories. In contrast, we do not understand well even basic physiological behavior in these organisms. This includes the widespread phenomenon of organic acid excretion. One strong hurdle to fully exploit the metabolic capacity of these organisms is the enormous, highly environment sensitive phenotypic plasticity. In this work we explored organic acid excretion in Penicillium ochrochloron from a new point of view by simultaneously investigating three essential metabolic levels: the plasma membrane H+-ATPase (PM); energy metabolism, in particular adenine and pyridine nucleotides (M); and respiration, in particular the alternative oxidase (R). This was done in strictly standardized chemostat culture with different nutrient limitations (glucose, ammonium, nitrate and phosphate). These different nutrient limitations led to various quantitative phenotypes (as represented by organic acid excretion, oxygen consumption, glucose consumption and biomass formation). Glucose-limited grown mycelia were used as the reference point (very low organic acid excretion). Both ammonium and phosphate grown mycelia showed increased organic acid excretion, although the patterns of excreted acids were different. In ammonium-limited grown mycelia amount and activity of the plasma membrane H+-ATPase was increased, nucleotide concentrations were decreased, energy charge (EC) and catabolic reduction charge (CRC) were unchanged and alternative respiration was present but not quantifiable. In phosphate-limited grown mycelia (no data on the H+-ATPase) nucleotide concentrations were still lower, EC was slightly decreased, CRC was distinctly decreased and alternative respiration was present and quantifiable. Main conclusions are: (i) the phenotypic plasticity of filamentous fungi demands adaptation of sample preparation and analytical methods at the phenotype level; (ii) each nutrient condition is unique and its metabolic situation must be considered separately; (iii) organic acid excretion is inversely related to nucleotide concentration (but not EC); (iv) excretion of organic acids is the outcome of a simultaneous adjustment of several metabolic levels to nutrient conditions.